2008
DOI: 10.1089/vbz.2007.0247
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Cats in Zoonotic Leishmaniasis in Portugal

Abstract: Leishmaniasis, caused by Leishmania infantum, is an endemic zoonosis in the Mediterranean basin. Dogs are considered the major host for these parasites, as well as the main reservoir for human visceral infection. In recent years, asymptomatic infection or clinical disease caused by L. infantum in cats has been reported in several countries where zoonotic leishmaniasis is present. The aim of the present study was to perform a leishmaniasis survey in cats from an endemic focus. Twenty-three adult stray cats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
4
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 11 publications
4
48
4
9
Order By: Relevance
“…Percentages superior to those obtained in our study were found in Portugal by Maia et al (2008), who observed 30.4% (7/23) felines carrying leishmaniasis. In Greece, Diakou et al (2009) verified that 3.87% (11/284) cats had anti-Leishmania antibodies.…”
Section: Epidemiologycontrasting
confidence: 84%
See 1 more Smart Citation
“…Percentages superior to those obtained in our study were found in Portugal by Maia et al (2008), who observed 30.4% (7/23) felines carrying leishmaniasis. In Greece, Diakou et al (2009) verified that 3.87% (11/284) cats had anti-Leishmania antibodies.…”
Section: Epidemiologycontrasting
confidence: 84%
“…The occurrence of leishmaniasis in domestic cats has been reported in a large number of countries (Mancianti, 2004;Maia et al, 2008;Silva et al, 2008). In our study, only the species Leishmania (L.) chagasi was found in the analyzed cats (Coelho et al, 2011c), which could be associated or not with other diseases (Coelho et al 2010).…”
Section: Epidemiologymentioning
confidence: 39%
“…In European countries, the seroprevalence of domestic cats to visceral leishmaniasis in endemic areas varies from 0.9% [6] to 4.29% in Italy [7] , 30.4% in Portugal [8] , 60% in Spain [9] and 6.7% in Jerusalem [10][11][12] . In the southwestern region of Brazil, the seroprevalence for visceral leishmaniasis in this Contents lists available at ScienceDirect was about 25% in domestic cats [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, epidemiological surveys using IFA and PCR revealed a ratio of 30.4% (7/23) in Portugal (MAIA et al, 2008), and 6.7% (7/104) in Israel using ELISA (NASEREDDIN et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The occurrence of visceral leishmaniasis in cats has been described in several countries (MANCIANTI, 2004;MARTÍN-SÁNCHEZ et al, 2007;MAIA et al, 2008;NASEREDDIN et al, 2008), including Brazil (SAVANI et al, 2004SILVA et al, 2008). Skin lesions have also been reported in cats with leishmaniasis (PENNISI et al, 2004).…”
Section: Introductionmentioning
confidence: 99%